Exploring Public Private Partnership Models for Funding of Universities in Nigeria - Niyi Jacob Ogunode; OBIAKOR, Mariagoretti Ijeoma (Research Parks Publishers, 2023)
The realization of university programme depends on adequate funding. Adequate funding is the life wire of the university system. No any meaningful development can be achieved in the universities education without adequate funds. Recently, the Nigerian universities have been experiencing problems of financial shortage. Many universities administrators in Nigeria cannot execute programme of the universities because of scarcity of funds. This paper explores various public-private partnership funding models options for the funding of universities in Nigeria. Secondary data collected from both print and online publications were used for the paper. The paper concluded that there are various Public-Private Partnership Funding Model options available for the funding of universities in Nigeria which include; Build, Operate, Transfer (BOT), Design, Build, Finance, Own (DFBO), Design, Build, Operate and Transfer (DBOT), Build, Own, Operate and Transfer (BOOT), Rehabilitate, Operate and Transfer (ROT), Joint Development Agreement (JDA), Operation and Maintenance (OM), Management/Lease Contract, Outsourcing, Leasing Contract, divestiture and concession.. The paper also established that universities in Nigeria can adopt public-private partnership funding models available to increase funds availability in the universities system, fund infrastructure facilities projects, increase research funding and increase communities services to the host communities across Nigeria. The paper recommended that the federal and state government should direct universities administrators to adopt the various Public Private Partnership (PPP) funding models available in the country to enhance implementation of teaching, research and community service programme and fund infrastructure facilities projects in the universities.